Peran Hakim Agung sebagai Pembaharu Hukum untuk Mewujudkan Pengadilan yang Bersih - Mashudi - (Faculty of Law, Trisakti University, 2014)
In the law country, obviously it needs a parlemental institution as an institution which has a main duty to obey the law as the people wanted. In globalization era now aday, cases of law, changement of law and law development happened in fast motion, they need faster judgement call, in this case, for cassation and judicial review. Great judges act to give sentence in concreto as a law reformation. Their law judgements will be applied and used as one of formal law sources in term of jurisprudence.To have honest court, it needs a good court system, so that it will create moral and honour Great judges.